Correlations of histomorphometrical indicators of spongiosa of the femur articular parts and the results of clinical and laboratory studies in patients with rheumatoid arthritis - Hryhorovskyi, Valeriy; Gerasimenko, Sergey; Panchenko, Sergey; Lyutko, Olga (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2015)
Histomorphometric characteristics of spongiosa (HCS) of the femur articular ends (FAE) are important for the evaluation of structural and functional state of bone tissue being potential bed for arthroplasty of the hip and knee joints. Purpose: based on pathohistological examination and correlative analysis of clinical, clinical and laboratory, and HCS of the FAE forming the hip and knee joints, to establish the relationship between indicators that are informative about the state of bone tissue of the articular ends. Methods: We investigated the HCS parameters (bone volume, osteoid surface, osteoclastic index) of the head and distal epiphysis of FAE removed during hip (24) and knee (31) arthroplasties. The results of clinical examinations (rheumatic process activity, the level of C-reactive protein (CRP), joint functional insufficiency (JFI), obtaining basis or hormone therapy), as well as ex vіvo cultivation of spongiosa bone marrow stromal cells. Results: for the head of the femur it was determined a negative with medium strength correlation between the degree of JFI and osteoclastic index. For the distal epiphysis it was shown a direct correlation of bone volume with osteoclastic index from the one side, and with process activity from the other one. There was determined an ambiguity of relations of laboratory and HCS-indices in particular the weak positive correlation between the CRP index and bone volume (unreliable for current number of observations). Conclusion: weighted HCS parameters in different parts of the femur was veraciously higher in spongiosa of the head than of the distal epiphysis. Majority of correlative connections between clinical, clinical and laboratory parameters, and HCS ones are ambiguous, except some pares correlation parameters of which correspond to the values of the correlation coefficient with average power or close to them.